2003
DOI: 10.1210/jc.2003-030646
|View full text |Cite
|
Sign up to set email alerts
|

Neurosteroids: Cerebrospinal Fluid Levels for Alzheimer’s Disease and Vascular Dementia Diagnostics

Abstract: A neurodegenerative disease such as Alzheimer's disease (AD) is associated with significantly higher dehydroepiandrosterone (DHEA) levels in cerebrospinal fluid (CSF). Because the human brain is known to transform DHEA into DHEA sulfate (DHEAS), 7 alpha-hydroxy-DHEA, 7 beta-hydroxy-DHEA, and 16 alpha-hydroxy-DHEA, it is possible that DHEA accumulation in the brain results from a decreased production of such metabolites. To test this hypothesis, we have measured and compared CSF levels of DHEA, DHEAS, 7 alpha-h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
55
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 82 publications
(64 citation statements)
references
References 44 publications
7
55
0
Order By: Relevance
“…A reduction in the CSF levels of DHEAS is present in mild to moderate AD patients (Kim et al, 2003) in spite of increases of DHEA plasma levels in such AD patients (Rasmuson et al, 2002). As a matter of fact, an increase of DHEA levels has also been detected in the cerebrospinal fluid of AD patients, while in the same patients the DHEAS levels were significantly reduced.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…A reduction in the CSF levels of DHEAS is present in mild to moderate AD patients (Kim et al, 2003) in spite of increases of DHEA plasma levels in such AD patients (Rasmuson et al, 2002). As a matter of fact, an increase of DHEA levels has also been detected in the cerebrospinal fluid of AD patients, while in the same patients the DHEAS levels were significantly reduced.…”
Section: Discussionmentioning
confidence: 97%
“…As a matter of fact, an increase of DHEA levels has also been detected in the cerebrospinal fluid of AD patients, while in the same patients the DHEAS levels were significantly reduced. Thus, it is possible that the DHEA accumulation in the brain and in the plasma results from a decreased production of its biologically active metabolites (Kim et al, 2003). These findings indicate that neuroprotection is mainly exerted by DHEAS while DHEA may exert only minor protective effects.…”
Section: Discussionmentioning
confidence: 98%
“…Interestingly, hippocampal PREGS concentrations have been shown to be negatively correlated with memory impairments in aged rats (Vallée et al 1997), strongly suggesting that hippocampal PREGS is important for memory processing in aged animals. In humans, changes in brain neurosteroid concentrations have been described in demented patients [Alzheimer's disease (AD)], with age-matched controls used as the reference group (Weill-Engerer et al 2002a;Kim et al 2003;Brown et al 2003). Weill-Engerer et al (2002a,b) reported decreases in the concentrations of PREGS and DHEAS in the striatum, hypothalamus (DHEAS only) and cerebellum of demented patients, consistent with the decrease in cerebrospinal fluid (CSF) DHEAS levels observed in patients with AD and vascular dementia (Kim et al 2003).…”
Section: Pathophysiological Implications For Age-related Sleep and Mementioning
confidence: 99%
“…Several other clinical studies have reported lower serum concentrations of DHEAS in patients with AD [14,[118][119][120], a reduction paralleled by decreases in the brain and cerebral spinal fluid [121,122]. For instance, Weill-Engerer and colleagues [108] reported that not only are brain levels of DHEAS significantly lower in AD, but also the lower levels are inversely correlated with the presence of phosphorylated tau and β-amyloid.…”
Section: Dhea and Admentioning
confidence: 97%
“…7α-hydroxy-DHEA may have more potent bioactivity and stronger neuroprotective and antiglucocorticoid effects than DHEA itself [152]. Interestingly, some investigators have hypothesized that the degree of metabolism of DHEA to 7α-hydroxy-DHEA is related to the pathology of AD [122,151,153,154]. This is evident in the study by Yau et al [151], which found that gene expression for cytochrome P4507b (which converts DHEA into 7α-hydroxy-DHEA) was significantly decreased in hippocampal dentate neurons from patients with AD when compared to controls [151].…”
Section: Dhea and Admentioning
confidence: 99%